An early childhood teachers teaching ability in project based science learning: A case on visible light. Issue 2 (February 2019) - Afifah, R N; Syaodih, E; Setiasih, O; Suhandi, A; Maftuh, B; Hermita, N; Samsudin, A; Handayani, H
Abstract: The research aims to describe teacher's ability in teaching science toward project based learning for early childhood (EC) students. The EC teacher's ability in term of using learning model are very useful. The instrument used in this study is teachers teaching ability assessment tool based project learning. This study was conducted on 2 teachers of early childhood education in Bandung. Design the research used is descriptive qualitative. The results obtained indicate that teachers teaching project based science learning have not been compatible with project based learning steps. This happens because the teacher is less understanding of project-based science learning. Thus the ability of early childhood education teachers to understand project based learning in project based science teaching is essential.